Arabidopsis Flowers Unlocked the Mechanism of Jasmonate Signaling - Browse, John (Plants (Basel), 2019)
The Arabidopsis male-sterile phenotype has been a wonderful model for jasmonate action in plants. It has allowed us to identify transcription factors that control gene expression during stamen and pollen maturation and provided for the discovery of the JAZ repressor proteins and the mechanism of jasmonate signaling. More recently, it has revealed intriguing details of the spatial localization of jasmonate synthesis and perception in stamen tissues. The extensive and thoughtful application of protein–protein interaction assays to identify JAZ-interacting partners has led to a much richer appreciation of the mechanisms by which jasmonate integrates with the actions of other hormones to regulate plant growth and physiological responses. This integration is strikingly evident in stamen and pollen development in Arabidopsis, which requires the actions of many hormones. Just as importantly, it is now evident that jasmonate has very different actions during flower development and reproduction in other plant species. This integration and diversity of action indicates that many exciting discoveries remain to be made in this area of jasmonate hormone signaling and response.